Amphiphilic Conjugated Polythiophene‐based Fluorescence "Turn on" Sensor for Selective Detection of Escherichia coli in Water and Milk. (26th May 2021) - Shim, Jimin; Tawfik, Salah M.; Thangadurai, Daniel T.; Lee, Yong‐Ill
Abstract : The ability to detect pathogenic microbes in water and food samples is of prominent interest, but it remains a great challenge. Herein, we report a simple fluorescence sensor based on amphiphilic conjugated polythiophene (ACPT) for the detection of gram‐negative pathogenic bacteria, Escherichia coli, in pH 7.0. The ACPT sensor was synthesized by the oxidative polymerization of water‐soluble thiophene monomers in an aqueous solution. The ACPT sensor undergoes the fluorescence " turn on " response at 432 nm upon the addition of E. coli . The ionic complex, which is generated by electrostatic interaction during the short incubation time of 15 min, resulting in the enhancement of the fluorescence intensity of ACPT. The application of ACPT enables the detection of E. coli pathogens in tap water and milk samples with good recoveries of 96.94–100.83% and 93.27–116.75%, respectively, and excellent reproducibility ( n  = 3, relative standard deviation [RSD] = 1.78%). The current findings pave the way for the promising application of a novel ACPT system that could be used in food safety and environmental monitoring. Abstract : A simple fluorescence sensor based on amphiphilic conjugated polythiophene (ACPT) was developed for the detection of gram negative pathogenic bacteria, Escherichia coli . ​